2002
DOI: 10.1021/jf0116808
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polysulfone in Controlled-Release NPK Fertilizer Formulations

Abstract: Encapsulation of fertilizers in polymeric coatings is a method used to reduce fertilizer losses and to minimize environmental pollution. Polysulfone was used for a coating preparation for soluble NPK granular fertilizer in controlled-release fertilizer formulations. The coatings were formed by the phase inversion technique (wet method). The influence of the polymer concentration in the film-forming solution on the physical properties of the coatings was examined. The coating structure controls the diffusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(96 citation statements)
references
References 7 publications
4
89
0
3
Order By: Relevance
“…Moreover, mixture of BF and organic fertilizers showed even more remarkable advantages in growth promotion in 60 d, suggesting that the combination of BF and organic fertilizers support plant growth in the long term better than the BF+IOF treatment. The result that the growth of pepper plants in BF+IOF is comparatively faster in the first 30 d and slows down in the later 30 d is in accordance with the report of Tomaszewska and Jarosiewicz (), that a majority part of chemical fertilizer is released to the soil within 5–30 d after application.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, mixture of BF and organic fertilizers showed even more remarkable advantages in growth promotion in 60 d, suggesting that the combination of BF and organic fertilizers support plant growth in the long term better than the BF+IOF treatment. The result that the growth of pepper plants in BF+IOF is comparatively faster in the first 30 d and slows down in the later 30 d is in accordance with the report of Tomaszewska and Jarosiewicz (), that a majority part of chemical fertilizer is released to the soil within 5–30 d after application.…”
Section: Discussionsupporting
confidence: 90%
“…Concomitantly, quantifications were performed for tests involving pure Hap and SSP as a control experiment. Urea release experiments were performed parallel with phosphorus solubilization tests according to the method adapted from Tomaszewwska and Jarosiewicz35. The concentration of urea in solution was determined by UV-Vis spectrophotometer (Shimadzu-1601PC).…”
Section: Methodsmentioning
confidence: 99%
“…7,8 It should also have a hardness that effectively protects the substrate (fertilizer), with good resistances to mechanical abrasion and moisture permeation. 9 In the specialized literature, some studies have been reported that propose various materials to coat nutrients. 10 However, in general, the recommendations indicate thick coatings, which reduce the total amount of nutrient present in the granule.…”
Section: Introductionmentioning
confidence: 99%